2017
DOI: 10.2147/tcrm.s132344
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol improves glycemic control in type 2 diabetic patients: a 6-month prospective interventional study

Abstract: Background and purposeTo investigate the effects of vitamin D supplementation on glucose homeostasis and lipid profile in type 2 diabetic patients who have vitamin D deficiency.Patients and methodsOne hundred twenty-five type 2 diabetic patients taking oral hypoglycemic agents as mono- or combination therapy were recruited from the diabetes and endocrinology clinic. Subject demographics, duration of diabetes, antidiabetic medication, body mass index (BMI), pulse, and blood pressure (BP) were assessed. Laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…In addition, the elevated intact parathyroid hormone (iPTH) observed in subjects with low 25(OH)D3 levels might play a causal role in the pathogenesis of increased adiposity (33). Similarly to our results, many studies have reported that patients with insufficient levels of vitamin D have high prevalence of dyslipidemia, they showed that the use of this vitamin might reduce levels of TG, TC, and might improve HDL-C level (34)(35)(36)(37). Vitamin D is shown to exert a role in the transportation of cholesterol by regulating the apolipoprotein A-1 levels, and it may act in the reduction of LDL-C uptake, may decrease the formation of foam cells, and may enhance the production of HDL-C.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the elevated intact parathyroid hormone (iPTH) observed in subjects with low 25(OH)D3 levels might play a causal role in the pathogenesis of increased adiposity (33). Similarly to our results, many studies have reported that patients with insufficient levels of vitamin D have high prevalence of dyslipidemia, they showed that the use of this vitamin might reduce levels of TG, TC, and might improve HDL-C level (34)(35)(36)(37). Vitamin D is shown to exert a role in the transportation of cholesterol by regulating the apolipoprotein A-1 levels, and it may act in the reduction of LDL-C uptake, may decrease the formation of foam cells, and may enhance the production of HDL-C.…”
Section: Discussionsupporting
confidence: 90%
“…of glycemic control refl ected by HbA1c is signifi cantly related to vitamin D level. The same thing also found in another study that there is a signifi cant relationship in the vitamin D supplementation to decrease HbA1c (7.9±1.7% vs 7.4±1.2%, p=0.001) (27).…”
supporting
confidence: 72%
“…Another study from Egypt investigated the effects of vitamin D supplementation on glucose homeostasis and lipid profile in 125 T2DM subjects having vitamin D deficiency. 15 Vitamin D3 replacement was associated with a significant increase in its level (14.0±4.0 vs 31.0 vs 7.9 ng/mL, P<0.001). This was associated with a significant reduction of HbA1c (7.9±1.7 vs 7.4%±1.2%, P=0.001).…”
Section: Discussionmentioning
confidence: 88%